ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG LISTING DI BEI PERIODE TAHUN 2013-2015 - Firstya Widiastri, 15.05.62.0002; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2017)
This study examines the factors that affect the value of companies in banking companies listed on the IDX period 2013-2015. This research is conducted in Bursa Efek Indonesia by using unit of analysis of banking company. Sampling method using purposive sampling, that is sample determination technique by using certain criteria. The relationship or influence between variables is explained by using multiple linier regression analysis method and hypothesis test (t test). The results showed that Return On Equity (ROE) has a significant negative effect on the value of the company. Loan to Deposit Ratio (LDR) and Net Profit Margin (NPM) have no effect on corporate value. Price Earnings Ratio (PER) and Earning Per Share (EPS) have a positive and significant impact on firm value.Keywords: Return On Equity, Loan to Deposit Ratio, Net Profit Margin, Price Earnings Ratio and Price to Book Value